2008
DOI: 10.1093/ajcn/87.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Meal-induced compositional changes in blood and saliva in persons with bulimia nervosa

Abstract: There were no apparent differences in the composition of blood and saliva between bulimia nervosa and control subjects, and meal-induced compositional changes in blood were not directly mirrored in saliva composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…These findings are in line with most of the studies which reported higher ghrelin levels in saliva compared to serum for healthy adults, epileptic patients, and patients with end-stage renal disease [2,[20][21][22]. In a study by Dynesen et al, ghrelin was found to be in the same range of concentrations in blood and saliva, both in healthy women and female patients with bulimia nervosa [17]. It has been assumed that the diffusion rate of ghrelin produced in salivary glands to saliva is probably higher than in plasma [2].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…These findings are in line with most of the studies which reported higher ghrelin levels in saliva compared to serum for healthy adults, epileptic patients, and patients with end-stage renal disease [2,[20][21][22]. In a study by Dynesen et al, ghrelin was found to be in the same range of concentrations in blood and saliva, both in healthy women and female patients with bulimia nervosa [17]. It has been assumed that the diffusion rate of ghrelin produced in salivary glands to saliva is probably higher than in plasma [2].…”
Section: Discussionsupporting
confidence: 86%
“…However, there are no reports about meal-induced changes of salivary ghrelin in obese individuals. In a study by Dynesen et al, salivary ghrelin concentrations were not suppressed after a standardized meal as demonstrated for serum ghrelin and did not differ significantly between healthy females and patients with bulimia nervosa [17]. By contrast, Gröschl et al showed a significant decline of both serum and saliva ghrelin 2 h after sugar load in healthy males and patients who underwent oral fructose and lactose tolerance test due to suspected carbohydrate malabsorption [11].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The composition of saliva can vary significantly depending on oral health and dietary regime [22]. Closely following ingestion of food significantly higher amounts of glucose in the saliva have been observed, up to around 400 lM (from originally~30 lM) [24]. In addition to [22].…”
Section: Miniature Efc Operating In Human Salivamentioning
confidence: 99%